2022
DOI: 10.3389/fphy.2022.861389
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Birefringence of Periodic Nanostructures in FTO Thin Film Fabricated by IR-UV Femtosecond Laser

Abstract: By using infrared to ultraviolet (IR-UV) femtosecond laser directing, periodic nanostructures were efficiently fabricated on an F-doped tin oxide (FTO) film with a thickness of 650 nm. The morphology of the nanostructures and duty cycle were studied in detail by changing the laser fluence and scanning speed, where three lasers with central wavelengths of 343, 515, and 1,030 nm were used in the experiments. Under the 515 nm laser irradiation with scanning speed of 0.01 mm/s and laser fluence of 23 mJ/cm2, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Efficient fabrication of regular and large-area LSFLs Laser processing parameters, including laser wavelength, fluence, and scanning speed, play crucial roles in the efficient and high-quality fabrication 30 . The transmittance of ITO film in the visible region is higher than 85%.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient fabrication of regular and large-area LSFLs Laser processing parameters, including laser wavelength, fluence, and scanning speed, play crucial roles in the efficient and high-quality fabrication 30 . The transmittance of ITO film in the visible region is higher than 85%.…”
Section: Resultsmentioning
confidence: 99%
“…While for ITO films with a thickness of 600 nm, the laser fluence required for processing LSFLs was higher than 1.0 J/cm 2 at a scanning velocity of 3 mm/s. The heat accumulation during laser processing was very serious, which resulted in irregular LSFLs [ 5 , 52 , 53 , 68 ]. ITO film with a thickness of 175 nm was suitable for processing LSFLs with extreme regularity.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, LIPSS features with a spatial period of 300 nm were obtained at a wavelength of 1030 nm, while irregular HSFL with a spatial period of 126 nm could be obtained when using a 343 nm laser wavelength. 39 In addition, studies carried out by Scorticati et al 54,55 showed the formation of LIPSS when SnO 2 thin films were structured with a 343 nm ps-laser (6.7 ps). In these works, the authors reported that as the LIPSS had a spatial period in the range of 50-80 nm, i.e.…”
Section: Topography Evolution Upon Laser Structuringmentioning
confidence: 99%
“…[36][37][38] To the best of our knowledge, only a few studies were published in which DLIP was employed to modify the optoelectronic characteristics of TCOs using stable and costeffective IR laser sources. 20,39 For instance, Zhang et al structured FTO thin films with a 1030 nm femtosecond laser, obtaining birefringence properties. The fabrication of nanogrooves with a spatial period of B300 nm was achieved and the birefringence (Dn) reached a value of 0.20.…”
Section: Introductionmentioning
confidence: 99%